Rancang Bangun Sistem Informasi Penjualan Pada UMKM MJ Sweet Berbasis Web - Angga Wahyu Prayoga; Azizah Nur Fatmawati (Jurnal Media Computer Science, 2026)
The MJ Sweet MSME represents a small-to-medium enterprise engaged in the production and distribution of assorted cakes and confectionery products. In its operational practices, the enterprise continues to encounter substantial challenges in managing product data, sales transactions, and promotional activities due to the absence of an integrated information system. This research aims to design and implement a web-based sales information system intended to streamline the management of products, transactions, and financial reporting in a more efficient, structured, and organized manner. The system development process employs the Waterfall model, encompassing sequential stages of requirement analysis, system design, implementation, and testing.The application was developed using the PHP programming language, MySQL as the database management system, and the Laravel framework, which together enable the creation of an interactive, responsive, and user-friendly interface. System evaluation was conducted through the Black Box Testing approach to validate the functional conformity of all system components with the established specifications. The testing outcomes demonstrated that all system features operated optimally without any functional discrepancies. Overall, the developed system effectively enhances sales operational efficiency, improves data accuracy, and provides significant convenience for both administrators and customers in executing online transactions.